Role of Ayurveda in the management of Vatashthila W. S. R. to benign prostatic hyperplasia: a review study - Gujjarwar, Shriniwas; ., Shalu (International Surgery Journal, 2022)
In Ayurvedic texts vatashthila [i.e.; benign prostatic hyperplasia (BPH)] is a one of major urinary disorder described in mutraghata (i.e.; decreased urine flow due to obstructionin urinary passage). It is a very major common problem in geriatric age group in males (usually in 60-70 years of age). Histo-pathologically the prevalence of BPH is age dependent, initiate usually after 40 years of age. More than 50% of men in their 60s and upto 90% of men in their 70s and 80s have some symptoms of BPH. In contemporary science conservative and surgical treatment are given to the patients suffering with BPH. The symptoms of vatashthila have been described in mutraghata resembles to the benign prostatic hyperplasia in modern science. The aim of the study is to focus on various studies done on vatashthila (i.e.; BPH) between 2016-2021. The various studies have been done on efficacy of Kanchnar guggulu, Trikantakadi guggulu, Veertarnadi gana kshaya, Varun bark decoction (Kwath), Ushiradi taila as Uttarbasti and Dhanyak gokshur ghrita yavkshar as Uttarbasti in the management of Vatashthila (BPH). These studies may be very beneficial to improve the tonicity of urinary bladder and to reduce the size of the prostate.